Aprovechamiento del relave minero en la fabricación de durmientes de hormigón en la planta de beneficio “Playitas”, Sector El Salado, Cantón Portovelo, Provincia de El Oro - Chinchay Ortega, Stillman Daniel (2025)
The present investigation titled “Utilization of Mining Tailings in the Production of Concrete Sleepers at the Playitas Beneficiation Plant, located in El Salado sector, Portovelo Canton, El Oro Province”, was developed based on qualitative and quantitative analysis, starting with a field phase which focused on the collection of samples and material for the development of the research in the tailings pond of the Playitas Beneficiation Plant and in the mining area Luis 3 of stone materials, located one kilometer from the processing plant. After that, in the laboratory phase, the different properties of the materials that make up the standard concrete with and without the application of mining tailings, the design of the concrete sleepers and the drafting of the data obtained and calculated were determined. First, the physical, chemical and mineralogical properties of the concrete component materials like sand, gravel and mining tailings, were characterized. This analysis allowed evaluating their characteristics from laboratory tests based on ASTM standards, corresponding to each test. Subsequently, in order to design the standard concrete mix with and without the addition of mining tailings, the properties previously studied were taken into consideration, applying the ACI-318 standard, the concrete dosage was evaluated. These mixtures were subjected to physical tests to assess the density of the fresh and hardened concrete as well as the workability, and mechanical tests to evaluate the strength of the designed concrete against simple compression and bending. Finally, a prototype concrete sleeper was designed based on the specifications and recommendations set by the AREMA standard, for the design of concrete and wood sleepers, the designs were calculated independently. Finally, an economic analysis of each type of sleeper was developed by establishing a comparison of values.